INDONESIAN PHONOLOGY ACQUISITION FOR FOUR YEARS OLD GIRLS - Wahidah Nasution (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The Phoneme is the smallest unit of a language. In the process of adapting the sound,the children with phonological disorder will be difficult to distiguish the sounds that have the same area of articulation or type of sound. This research method is a case study with the research subject is Leticia Unna Alfatunnisa; a four years child. The results show that Una has acquired most of the phonemes in Indonesian. Una has acquired all the vowels, and most of the consonants. This occurs due to phonological disorders due to age factors which result in the speech apparatus or muscles used for speaking (speech motor) being incomplete or not fully developed; from the arrangement of the teeth, the shape of the jaw, to the tongue which may still be stiff.